Identification and Classification of Technical Lignins by means of Principle Component Analysis and k‐Nearest Neighbor Algorithm. Issue 8 (5th August 2021) - Fink, Friedrich; Emmerling, Franziska; Falkenhagen, Jana
Abstract: Invited for this month's cover is the group of Dr. Jana Falkenhagen at the Bundesanstalt für Materialforschung und ‐prüfung in Berlin (Germany). The cover picture shows an artistic map like those found in many novels. The rivers serve as natural borders to separate different types of plants, such as softwood, hardwood, straw and grass. The idea for this abstract illustration comes from the core illustration of the work on which it is based. Read the full text of their Full Paper at 10.1002/cmtd.202100028 . Abstract : "… In this work, technical lignins were measured with infrared spectroscopy and then a mathematical model was created for classifying these models… ." Find out more about the story behind the front cover research at 10.1002/cmtd.202100028 .